The effect of sperm DNA fragmentation on intracytoplasmic sperm injection outcome - Kareim Khalafalla (14148807) (2021)
Our study objective was to assess the effect of various sperm DNA fragmentation levels on clinical intracytoplasmic sperm injection outcome. This retrospective study included 392 patients who underwent ICSI and performed sperm DNA fragmentation testing before the procedure. Based on sperm DNA fragmentation cut-off values, the patients were differentiated into 3 groups as <20%, 20%–30% and >30%. According to the female status, patients were differentiated into favourable group (n = 259) with female age <35 years and anti-Mullerian hormone level ≥7.1 pmol/L; and unfavourable group (n = 133) with female age ≥35 years and anti-Mullerian hormone level ≤7.1 pmol/L. The patient's medical records were reviewed, and patient's demographic, laboratory data including semen analysis, sperm DNA fragmentation determined by means of sperm chromatin dispersion, hormonal profile and data regarding intracytoplasmic sperm injection cycle were collected. This cohort reported that the clinical reproductive outcomes of intracytoplasmic sperm injection showed no statistical significance with increase sperm DNA fragmentation levels. In sperm DNA fragmentation above 30%, favourable females had significantly higher clinical pregnancy rate and live birth rate than unfavourable females, while fertilisation rate and miscarriage rate showed no significance between the subgroups. High sperm DNA fragmentation is linked to poor semen parameters. Other Information Published in: Andrologia License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/and.14180